2023
DOI: 10.1111/ajd.14019
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab treatment in combination with any other biologics: Is it really a safe duo?

Abstract: Background: Chronic spontaneous urticaria (CSU) is a mast cell-mediated disease, which is sometimes associated with various inflammatory disorders.Omalizumab is a commonly used biological agent, which is a recombinant, humanized, monoclonal antibody against human immunoglobulin E. However, there are only few reports about the combination of omalizumab for CSU with any other biologics for accompanying inflammatory diseases in the literature. The aim of this study was to evaluate the patients whose treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(45 reference statements)
1
1
0
Order By: Relevance
“…The safety of omalizumab is further bolstered by its use with concomitant systemic steroids and Janus kinase inhibitors (eg, baricitinib) in severely ill patients with multiple preexisting comorbidities (including advanced and/or metastatic cancer in 9/40 patients). These results correspond to observational studies that have reported the safe use of omalizumab (for its existing indications) in combination with other biologics and in severe COVID-19 illness [ 15 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…The safety of omalizumab is further bolstered by its use with concomitant systemic steroids and Janus kinase inhibitors (eg, baricitinib) in severely ill patients with multiple preexisting comorbidities (including advanced and/or metastatic cancer in 9/40 patients). These results correspond to observational studies that have reported the safe use of omalizumab (for its existing indications) in combination with other biologics and in severe COVID-19 illness [ 15 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…Although detailed guidelines are available for management of omalizumab [ 132 ], there are still unmet needs that should be addressed with future research. Areas that we believe could warrant more information to optimize use of omalizumab include the potential role of CSU pathogenesis in an individual (including autoallergy, anti-IgE antibodies, and angioedema) on the response to omalizumab; combination treatment (especially with other biologics [ 133 ]) for patients with comorbidities or slow responders; influence of pregnancy (by an initial analysis, pregnancy outcomes for patients with CSU treated with omalizumab were similar to patients with asthma where no increased risk was observed [ 134 ]); and the impact of race on access [ 135 ] and response.…”
Section: Clinicians’ Perspectivementioning
confidence: 99%